Ferroelectric photovoltaic effect engineered by phase transition and defect neutralization in K0.5Na0.5NbO3 film - Jiayi Zhang; Yaping Liu; Bo Yang; Shifeng Zhao (Results in Physics, 2024)
As an excellent light transmission material, K0.5Na0.5NbO3 (KNN) shows considerable potential in ferroelectric photovoltaics. However, poor leakage and non-intrinsic polarization limit their photoelectric conversion since they play important roles in the generation, separation and transport of photogenerated carriers. This work realizes the simultaneous improvement of bandgap, ferroelectric and leakage by the introduction of charged group BiFeO3 (BFO), which neutralizes the defects and reduces the leakage current of the films by about two orders of magnitude and increases the remanent polarization to 15.4 μC/cm2 due to the phase transition. Meanwhile, the addition of Fe also introduces impurity energy levels into the KNN films and reduces the bandgap. The open-circuit voltage of the 0.98KNN-0.02BFO film is increased by about 2.5 times. This work provides a feasible way to enhance the ferroelectric photovoltaic performance of KNN films and accelerate their application.